Innovation centers in Malaysia: a review - Anuar, Rashidah Nural (Information Engineering Research, 2012)
The government plans to establish a National Innovation Center (NIC) and a network of Centers of Innovation Excellence while Malaysia march to the next phase of economic development that is transforming from resource-based to innovation-based economy. Innovation Centers (ICs) have a crucial role to play in the successful commercialization of inventions and technology arising from research, business and development (RB&D) in order to establish NIC in the innovation led economy. In Malaysia, there are number of existing ICs operated by higher institution of learning and research centers such as SIRIM and FRIM. However, the key issue is whether such ICs can work in tandem with soon to be established. This study investigates the actors involved in these centers and their roles in innovation systems in Malaysia environment.